Brain Perfusion Mediates the Relationship Between miRNA Levels and Postural Control. Issue 1 (26th October 2020) - Chen, Yufen; Herrold, Amy A; Martinovich, Zoran; Bari, Sumra; Vike, Nicole L; Blood, Anne J; Walter, Alexa E; Harezlak, Jaroslaw; Seidenberg, Peter H; Bhomia, Manish; Knollmann-Ritschel, Barbara; Stetsiv, Khrystyna; et al.
Abstract: Transcriptomics, regional cerebral blood flow (rCBF), and a virtual reality-based spatial motor task were integrated using mediation analysis in a novel demonstration of "imaging omics." Data collected in National Collegiate Athletic Association (NCAA) Division I football athletes cleared for play before in-season training showed significant relationships in 1) elevated levels of miR-30d and miR-92a to elevated putamen rCBF, 2) elevated putamen rCBF to compromised Balance scores, and 3) compromised Balance scores to elevated microRNA (miRNA) levels. rCBF acted as a consistent mediator variable (Sobel's test P  < 0.05) between abnormal miRNA levels and compromised Balance scores. Given the involvement of these miRNAs in inflammation and immune function and that vascular perfusion is a component of the inflammatory response, these findings support a chronic inflammatory model in these athletes with 11 years of average football exposure. rCBF, a systems biology measure, was necessary for miRNA to affect behavior.